(untitled) (Future Cities and Environment, 2020)
Gas cycles, in their ideal form, promise the highest efficiency heat pump and external heat engine systems. The Ericsson and Stirling cycle promise Carnot efficiency, yet their seeming simplicity present significant engineering challenges in implementation. The primary challenge of both cycles is isothermal compression and expansion where finite time and the mechanical system’s insufficient surface area prevent ideal performance. Liquid flooding of the Ericsson cycle has been explored previously. Flooding with a high heat capacity liquid in effect increases the surface area for heat exchange, yet the experimental mechanical system uncounted significant losses, preventing suitable performance. This paper models a novel gas cycle system that combines aspects of the reverse Brayton air cycle and the Liquid Flooded Ericsson cycle. The enthalpy model in EES (Engineering Equation Solver) allows optimization of possible cycle arrangements and yields an optimal arrangement that constitutes a new gas cycle utilizing liquid flooding to achieve superior performance in a simpler cycle that previously envisioned. Possible applications of the new cycle include heat pump and external heat engines.